The fundamental role of Screen Quota in Brazil - Cardoso, Vivianne Lindsay [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Arquitetura Artes & Comun, 2024)
Based on an exploratory survey and Brazilian regulations in force between the years 2019 and 2022, and the years 2023 and 2024, the dialectical methodology is applied, through Marxist bases, in the search to understand, based on the political propositions of the presidents in the periods, how the standardization of the Screen Quota applied to cinema in Brazil achieves strategic and social role for contemplation in the access and consumption of Brazilian cinematographic production. It is concluded that the measure is essential for the development of national cinema, but the dependence on regulatory measures by decree or temporary must be reconsidered, ensuring that the national cinematographic market is not conditioned to the interests and political ideologies of the president in office.
Keywords: Communication and Culture Policies; Cultural diversity; Screen Dimension; Cinema and Cultural Industry